GENDER NEUTRALITY IN TOURISM LANGUAGE: A LINGUISTIC APPROACH - Miyassarov Eldor Amanovich (Modern American Journals, 2025)
This article analyzes the linguistic features of language used in the field of tourism in relation to gender neutrality. It examines the growing tendency to use neutral forms instead of gender-specific expressions in texts directed at guests and in promotional language. Furthermore, the article assesses the inclusivity level of tourism language based on gender sensitivity and cultural adaptability.
Keywords: gender neutrality, linguistics, tourism discourse, language policy, inclusive language, intercultural communication, terminology.